2021
DOI: 10.1007/s00586-021-06957-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends of epidemiological characteristics of traumatic spinal cord injury in China, 2009–2018

Abstract: Objective We focus on providing the first comprehensive national dataset on the incidence, injury aetiology and mortality of TSCI in China. Methods A multi-stage stratified cluster sampling method was used. We included TSCI cases from all hospitals in three regions, nine provinces and 27 cities in China via search of electronic medical records and retrospectively analysed the characteristics of TSCI in China from 2009 to 2018. We estimated the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Spinal cord injury (SCI) is a devastating trauma to the central nervous system (CNS), characterized by severe motor, sensory and autonomic dysfunction. In China, there were 10,074 cases of traumatic SCI in 2018 with a total estimated incidence of 66.5 cases per million in population, and the number is still rising ( Hao et al, 2021 ). However, its treatment is still a major problem in this field, and there is no effective cure currently ( Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a devastating trauma to the central nervous system (CNS), characterized by severe motor, sensory and autonomic dysfunction. In China, there were 10,074 cases of traumatic SCI in 2018 with a total estimated incidence of 66.5 cases per million in population, and the number is still rising ( Hao et al, 2021 ). However, its treatment is still a major problem in this field, and there is no effective cure currently ( Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2017 ; Khorasanizadeh et al, 2019 ). The incidence of SCI is high, approximately 23.7/million in China ( Hao et al, 2021 ). Over the past decade, a flourishing number of novel strategies have been demonstrated that could promote functional recovery after spinal cord injury in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, there were 27.04 million (24.98–30.15 million) SCI cases globally, including 0.93 million (0.78–1.16 million) new cases. Traumatic SCI in China showed an increasing trend from 2009 to 2018, with an estimated 66.5 cases/million population (95% confidence interval, 65.2–67.8) (Hao et al, 2021 ). SCI can impose an enormous physical, emotional, and financial burden on patients, families, and society (Badhiwala et al, 2019 ; Hejrati and Fehlings, 2021 ).…”
Section: Introductionmentioning
confidence: 99%